Efektifitas Penggunaan Metode Smart Energy (REIKI) Sebagai Alternatif Preventif Hyperglikemia Pasien Diabetes Melitus Tipe 2 - Aprilia Susanti; Dyah Rohmawati; Amik Muladi (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2019)
DM affects many people in the world and is one of the biggest problems for the nation. Some treatments ranging from medical to non-medical (alternative actions) have been carried out by each individual to be able to recover from the disease. Alternative and complementary therapies are therapies that are in great demand by people throughout the world, not least in Indonesia because they are relatively cheap and safe. One alternative therapy that can be done is by the